Design and analysis of a small satellite design hosting lidar sensor for data acquisition aimed at environmental protection - Paschalidis Maria; Kolios Stavros (E3S Web of Conferences)
This study presents the design and analysis of a small satellite design hosting a Lidar sensor for data acquisition aimed at environmental protection. The project explores the CubeSat technology, beginning with an overview of the international and Greek space sectors, the emergence of the “New Space” industry, and its economic impacts. The design focuses on the development and integration of the Lidar sensor within a CubeSat framework, detailing the historical context, engineering standards, and the development lifecycle of CubeSat designs. Key elements of the study include a thorough examination of the CubeSat’s subsystems, such as the payload (Lidar sensor), orbit determination and control (ADCS), propulsion, telecommunications, thermal protection, onboard computing, and power systems. The study also covers design planning, software development, cost estimation, and the identification of potential challenges. Furthermore, the research delves into the operational principles of Lidar technology, its significance in science and research, and its comparison with other data transmission technologies. The study also addresses advanced data analysis techniques for Lidar sensor data, focusing on signal processing, object detection, and feature extraction. The final section assesses the role of satellite data in C6ISR (Command, Control, Communications, Computers, Cyber, Intelligence, Surveillance, and Reconnaissance) information management systems and their applications in Greek spotlight. It explores the integration of satellite imagery with artificial intelligence to enhance data analysis and decision-making. Overall, this comprehensive study aims to contribute to the advancement of CubeSat designs equipped with Lidar sensors, providing valuable insights into technological innovations and their applications in environmental protection